Perceived Opportunities by Social Enterprises and their Effects on Innovation - Bartha, Zoltan; Bereczk, Ádám (Theory, Methodology, Practice – Review of Business and Management, 2019)
Social enterprises can play an important role in reducing inequality within a society and can also contribute to long-term economic development. Using a database based on the responses of 220 Hungarian social enterprises we first identify the business opportunities that they perceive. We conclude that social enterprises operating in different legal forms have different perceptions of their opportunities, and we speculate that this has an effect on their innovation activity as well. It is striking that – with the exception of social cooperatives – none of the Hungarian social enterprises see current or future social and/or market needs and demand as a major opportunity. This suggests that only social cooperatives have the incentive to focus their innovation efforts on social and market needs. Almost all social enterprises, on the other hand, have high expectation for European Union funds; the threat is that social innovation is driven by the targets set by the authorities allocating European funds, instead of the needs of the society.